2015
DOI: 10.1111/ppl.12391
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of a glucosyltransferase gene, LcUFGT1, involved in the formation of cyanidin glucoside in the pericarp of Litchi chinensis

Abstract: Anthocyanins generate the red color in the pericarp of Litchi chinensis. UDP-glucose: flavonoid 3-O-glycosyltransferase (UFGT, EC. 2.4.1.91) stabilizes anthocyanidin by attaching sugar moieties to the anthocyanin aglycone. In this study, the function of an UFGT gene involved in the biosynthesis of anthocyanin was verified through heterologous expression and virus-induced gene silencing assays. A strong positive correlation between UFGT activity and anthocyanin accumulation capacity was observed in the pericarp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 43 publications
3
44
0
Order By: Relevance
“…Previous studies indicated that the expression of LcUFGT , LcF3H , LcDFR , LcGST , and their regulatory gene LcMYB1 were up-regulated as the fruit developed toward full maturity (Wei et al, 2011; Lai et al, 2014; Li et al, 2015; Hu et al, 2016). In the present study, the expression of miR156a was enhanced with the accumulation of anthocyanins, while its target genes LcSPL1 / 2 were opposite ( Figures 3C,D ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicated that the expression of LcUFGT , LcF3H , LcDFR , LcGST , and their regulatory gene LcMYB1 were up-regulated as the fruit developed toward full maturity (Wei et al, 2011; Lai et al, 2014; Li et al, 2015; Hu et al, 2016). In the present study, the expression of miR156a was enhanced with the accumulation of anthocyanins, while its target genes LcSPL1 / 2 were opposite ( Figures 3C,D ).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the delicious taste, attractive red skin of litchi is another important aspect of the fruit quality. Recently, the gene involved in anthocyanin biosynthesis and sequestration from litchi has been reported (Wei et al, 2011; Lai et al, 2014, 2015, 2016; Li et al, 2015; Hu et al, 2016). However, the mechanism of miRNAs regulating anthocyanin biosynthesis in litchi has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Many regulation genes involved in anthocyanin biosynthesis have been identified in fruits such as peach (Tuan et al , Zhou et al ), grape (Kobayashi et al , Deluc et al , Hichri et al , Matus et al , Perez‐Diaz et al ), apple (An et al , Chagne et al ), pear (Wang et al , Zhai et al ), litchi (Lai et al , Lai et al ) and Myrica rubra (Liu et al , Huang et al ). However, few studies have reported on the functional characterization of the structural gene families in fruiting plants (Gonzalez et al , Cheng et al , Li et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Glycosylation is known not only to stabilize anthocyanins but also to serve as a signal for their transport to the vacuole (Ono et al ); thus, it plays an important role in the accumulation of anthocyanins in plants. In addition, the expression of UFGT genes has been shown to be one of the most closely regulated steps in the anthocyanin biosynthetic pathway (Boss et al , Griesser et al , Cutanda‐Perez et al , Wang et al , Tuan et al , Li et al ). Plants with mutations in glycosyltransferases ( GTs ), such as bronze1 (Fedoroff et al ) and ANL1 (Kubo et al ), do not accumulate anthocyanins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation